Modeling, control and electromagnetic transient simulation of the doubly fed induction generator-based wind energy generation system. (March 2014) - Han, Yang; Shen, Pan
This paper presents the dynamic modeling and the stator-voltage-aligned control (SVAC) strategies of the doubly fed induction generator (DFIG)-based wind energy generation system (WEGS). The state-space dynamic model of the DFIG is derived in the synchronous d-q reference frame. The control strategies of the DFIG-based WEGS includes three parts, namely, the network-side converter (NSC) control, the rotor-side converter (RSC) control and the maximum power-point tracking (MPPT) algorithm. The NSC and RSC control algorithms are implemented based on the internal model control principle. The SVAC algorithm is devised for the RSC, where the positions of the stator and rotor voltage-vectors are referenced to the stator-frame to simplify the controller. The hill-climbing method is adopted for the MPPT algorithm, and the iteration procedure for searching the optimal operation point is discussed. The simulation results obtained from the electromagnetic transient program (EMTP-ATP) are provided, which validates the effectiveness of the control algorithms. The theoretical analysis and EMTP-based digital simulation can be widely applied for the grid-connected converters in renewable generation and smart grid applications.